Modern NMR techniques for synthetic chemistry - Fisher, J. (New directions in organic & biological chemistry)
"This book illustrates how the key analytical technique, NMR spectroscopy, may be used to determine the abundance, size, shape, and function of organic molecules. It provides the reader with a physical picture for the NMR technique used (pictorial rather than mathematical), indicating the most common pulse sequences, some practical information as appropriate, followed by illustrative examples. This format is followed for each chapter so that the reader may go straight to practical and theoretical details as appropriate"--